Updates on Translational Research on Prevention of Polyps and Colorectal Cancer - Stoffel, Elena M. (Clinics in Colon and Rectal Surgery, 2018)
Morbidity and mortality from colorectal cancer (CRC) can be effectively reduced through early detection and prevention. To date, strategies for managing CRC risk have focused primarily on secondary prevention, through screening asymptomatic individuals for colorectal neoplasia. In the United States, implementation of screening among individuals age ≥50 has led to not only decreased CRC-related mortality but also reduced CRC incidence through colonoscopic removal of precancerous polyps. In contrast to screening's endpoint of early detection, the goal of primary prevention of CRC is to arrest and/or reverse colorectal carcinogenesis. Observational studies and randomized clinical trials continue to examine effects of specific pharmacologic agents (chemoprevention) and dietary interventions on development of advanced colorectal neoplasia. This review will present an overview of strategies for primary and secondary prevention of CRC, including endoscopic, pharmacologic, and dietary interventions.
Keywords: primary prevention; colorectal cancer; chemoprevention; colonoscopy